The Effectiveness Of Implementing Gdevelop-Based Educational Games In Learning Science With The Theme Of Light And Sound Waves In Elementary Schools - Swandi, Ahmad; Arsyad, Susalti Nur; Fauzan, Arief; Viridi, Sparisoma; Rahmadhanningsih, Sri; Iren, Febrianti (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
The use of digital-based science learning media in elementary schools is currently not maximized and is still monotonous which makes students less interested and quickly feel bored in participating in learning. The application of interactive learning media accompanied by games (educational games) is an alternative learning that needs attention. The purpose of this study was to determine the validity and effectiveness of implementing a GDevelop-based educational game in science learning on the theme of light and sound waves for grade IV in elementary schools. The research sample was 20 fourth grade students of SD Negeri Lariang Bangi. The validity of educational games is determined based on the average percentage of each aspect that contains several criteria. Meanwhile, the effectiveness of educational games can be seen from the increase in learning outcomes obtained after trials. This study uses a pre-experimental research method that uses quantitative data analysis techniques. The data collection technique uses tests, namely pretest and posttest. The results for the validity of educational game programs and materials obtained an average percentage of 86.4 and 88.36 respectively. Meanwhile, the test results showed that the average pretest and posttest scores were 37.5 and 82.5, respectively. Thus it can be concluded that the use of GDevelop-based educational game media on the science learning outcomes of fourth grade students at SDN Lariang Bangi 1 is proven to be valid and effective. This educational game can be used as an alternative learning media to create an active, fun and interesting learning atmosphere